CONTRIBUCIÓN AL DESARROLLO DE LA BIOTECNOLOGÍA DESDE LA EDUCACIÓN EN LOS NIVELES DE LA BÁSICA Y MEDIA - Valbuena Ussa, Edgar Orlay (Tecné, Episteme y Didaxis: TED, 1998)
The article presents the generalities of Biotechnology (definition, main applications and reaches), difficulties about its deficient development in Colombia. It proposed the realization of pedagogical projects with students enrolled on basic and middle education, with the goal to contribute to the solution about Natural Science teaching problems, and the development of Biotechnology in Colombia. A reflection is made about an experience with high school students on the frame of a pedagogical project that implied a work dealing contextualization and biotechnological applications. Other elements are presented in general way to contribute to the development in Biotechnology from educational aspects.